2006
DOI: 10.1161/01.hyp.0000224283.76347.8c
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Pressure–Independent Reduction in Carotid Stiffness After Long-Term Angiotensin-Converting Enzyme Inhibition in Diabetic Hypertensives

Abstract: Abstract-Hypertension and diabetes are associated with an increased arterial stiffness. A direct blood pressureindependent effect of angiotensin-converting enzyme inhibitors on arterial stiffness has never been unequivocally demonstrated. In this mechanistic study, we used an experimental design in which patients responding to 1 month treatment with 4 mg perindopril were randomized double-blind to either 4 mg perindopril or 8 mg perindopril for 6 months. We determined carotid distensibility with echotracking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(92 citation statements)
references
References 41 publications
4
80
0
8
Order By: Relevance
“…Hypertension is accompanied by the reduced arterial elasticity and impaired endothelial function, which synergistically contribute to the pathogenesis of vascular disease. 1,6,9,19 In our study, hypertensive patients displayed both elevated levels of circulating EMPs and faster baPWV, which was consistent with the earlier studies. 19,20 Therefore, it is believed that antihypertensive treatment for patients with hypertension should restore the vascular dysfunction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hypertension is accompanied by the reduced arterial elasticity and impaired endothelial function, which synergistically contribute to the pathogenesis of vascular disease. 1,6,9,19 In our study, hypertensive patients displayed both elevated levels of circulating EMPs and faster baPWV, which was consistent with the earlier studies. 19,20 Therefore, it is believed that antihypertensive treatment for patients with hypertension should restore the vascular dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…1 Although antihypertensive pharmacotherapy with the specific and arbitrary goal to modify BP profiles significantly reduced vascular events, emerging evidence indicates that with equivalent effects on lowering blood pressure, some but not all antihypertensive agents, lead to more reduction of vascular events. 2,3 This apparently beneficial effects beyond BP lowering may be, at least in part, because of further improvement of agent-related vascular properties, [2][3][4][5][6] suggesting that the evaluation of vascular function may be useful complement to brachial BP levels, and may provide more sensitive and specific markers for the vascular risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,[11][12][13][14]39 Recent data support that quinapril and captopril are equally efficient in modifying important surrogate end points with prognostic significance, such as left ventricular mass. 11 On the other hand, some studies have underscored that an improvement of arterial function in hypertensives may benefit prognosis, 5,7 but there are no trials to directly compare different ACEIs with regard to outcomes.…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%
“…8,50 We used telmisartan 80 mg, since this dose may result in a greater arterial effect compared with lower doses. 50 On the other hand, studies that compared the acute endothelial effects of different ACEIs showed that increasing the dose of the low-tissue affinity ACEI does not modify the effect on arterial function.…”
Section: Specific Comments -Limitationsmentioning
confidence: 99%
See 1 more Smart Citation